Improving job performance in Islamic Universities through Islamic work ethics, spiritual values, and organisational commitment - Hulaify, Akhmad; Al Hadi, M. Qoshid; Affandi, Muchammad Taufik (al-Uqud : Journal of Islamic Economics, 2024)
According to organisational equilibrium theory, this research examines the role of organisational commitments in mediating Islamic work ethics and spiritual values on job performance in Islamic universities. This research used a sample frame of 93 lecturers from Islamic universities in Banjarmasin. Furthermore, the hypotheses were examined using SmartPLS version 3. The findings showed that organisational commitment successfully mediates the relationship between Islamic work ethic and spiritual values toward job performance. This result provides a better understanding of how the human resources department can explore motivation techniques to improve organisational outcomes, particularly organisational commitment. This research offers a significant advancement for organisational commitment research. This finding also attempts to make Islamic universities that encourage and manage their lecturers' performance becomes competitive universities in managing organisational culture.